How to Debunk WTC Thermite - Ryan, Kevin (Dig Within, 2013)
The evidence for the presence of thermite at the World Trade Center (WTC) on 9/11 is extensive and compelling. This evidence has accumulated to the point at which we can say that WTC thermite is no…
Keywords: 911; kevin ryan; thermite; zionism